2018
DOI: 10.15171/apb.2018.071
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Cytotoxicity of Folate-Conjugated Bismuth Oxide Nanoparticles on KB and A549 Cell Lines

Abstract: Purpose: Lately, bismuth-based nanomaterials have been widely utilized in medical researches such as imaging, drug delivery and radio-sensitization. Despite their advantages, bismuth-based compounds have shown toxic effects in humans. There are few studies on cytotoxicity effects of bismuth oxide (Bi2O3) nanoparticles (NPs) in-vitro. In this study, we aimed to investigate cytotoxicity of bare and also folate and 5-aminolevulinic acid (5-ALA)-conjugated Bi2O3 NPs on nasopharyngeal carcinoma (KB) and lung cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The after effects of cytotoxicity screening, accordingly, could choose which materials are to be exposed to a decontamination procedure. 33 Therefore, this needs a concern relating to the toxicity effect of natural compounds. Zebrafish model is one of toxicity tests to determine toxicity effect of materials which is derived from natural products because it is easy to be applied and utilized as important model for understanding the mechanisms of development and diseases such as cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The after effects of cytotoxicity screening, accordingly, could choose which materials are to be exposed to a decontamination procedure. 33 Therefore, this needs a concern relating to the toxicity effect of natural compounds. Zebrafish model is one of toxicity tests to determine toxicity effect of materials which is derived from natural products because it is easy to be applied and utilized as important model for understanding the mechanisms of development and diseases such as cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that oxidative stress plays an important role in many complications such as diabetes, atherosclerosis, cancer as well as aging. Since, NPs may induce excessive ROS production in the nervous system with their ability to cross blood brain barrier, neurodegenerative diseases such as Parkinson and Alzheimer could be a consequence of NP toxicity (Sorg 2004;Schrand et al 2010;Afanas'ev 2011). Ahamed et al (2019 reported oxidative stress mediates the cytotoxic effects of Bi 2 O 3 -NPs in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress can trigger signalling pathways of MAPK8, and transcription factors such as NF-kB and TNF-α; and finally release of pro-inflammatory cytokines and some critical chemokines (Roach et al 2002;Shishodia and Aggarwal, 2002). Ahamed et al (2019) indicated the role of Bax/Bcl-2 pathway in cell death. Several reports indicated that NPs such as titanium dioxide (Monteiller et al 2007), carbon black (Niwa et al 2008) and crystalline silica (Rao et al 2004) induced strong pro-inflammatory responses; however, in the present study Bi 2 O 3 -NPs induced pro-inflammatory response is evaluated for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxicity was ascribed to the disruption of mitochondrial and lysosomal functions by reactive oxygen species with increased malondialdehyde/8-hydroxydeoxyguanine levels and decreased glutathione levels Mahmoud et al (Chemla et al, 2019). Akbarzadeh et al also demonstrated the cytotoxicity of naked or folate-conjugated Bi 2 O 3 NPs at >50 μg/ml in A549 and KB cells in a concentration-dependent manner (Akbarzadeh et al, 2018). Alternatively, bismuth lipophilic NPs (BisBAL NPs) can selectively prevent MCF-7 breast cancer cell growth, and exposure to BisBAL NPs caused loss of cell membrane integrity and fragmentation of tumor cell DNA, which were genotoxic to breast cancer cells, causing cell apoptosis at 10 μM (Hernandez-Delgadillo et al, 2018).…”
Section: In Vitro Toxicity Of Bismuth Npsmentioning
confidence: 99%